2016
DOI: 10.5039/agraria.v11i2a5370
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da biomassa em híbridos de capim-elefante para fins energéticos

Abstract: RESUMOAlém do uso como forrageira, o capim-elefante vem sendo utilizado como fonte de energia alternativa. Isso se deve pela sua alta capacidade de produção de biomassa. É desejável que essa biomassa tenha alto teor de fibras e baixo de cinzas, por isso há necessidade de se obter materiais genéticos com essas características. Com isso, o objetivo deste trabalho foi avaliar as características químicas dos híbridos de capim-elefante e dos seus genitores para produção de biomassa energética. O experimento foi con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Sousa et al. (2016) evaluated eight EG varieties and found average contents of 40.3% CEL, 28.5% HCEL, 8.8% LIG and 4.4% ash. Rocha et al.…”
Section: Resultsmentioning
confidence: 99%
“…Sousa et al. (2016) evaluated eight EG varieties and found average contents of 40.3% CEL, 28.5% HCEL, 8.8% LIG and 4.4% ash. Rocha et al.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental plots were arranged in rows that were 1.5 cm apart and 3 m long. The use of two replications in elephant grass cultivation has been widely supported by previous studies conducted by Souza et al (2017), Stida et al (2018), Daher et al (2020), Rodrigues et al (2020) and Vidal et al (2023b).…”
Section: Location Design Population and Evaluated Traitsmentioning
confidence: 88%
“…The significant interaction between genotypes and harvests indicates that there was a change in the classification of genotypes in different harvests. Sousa et al (2016) evaluated elephant grass genotypes and also observed that, some were influenced by the evaluation harvest which is related to environmental conditions (temperature, luminosity, rainfall distribution), prevailing during the crop growth period.…”
Section: Combined Analysis Of Variancementioning
confidence: 99%